Predatory states : Operation Condor and covert war in Latin America - McSherry, J. Patrice (Rowman & Littlefield Publishers, Inc., 2005)
"This work makes a compelling case that U.S. forces secretly condoned and assisted the implementation of Operation Condor, a covert Latin American military network created during the Cold War to facilitate the seizure and murder of political opponents across state borders. Drawing on a wealth of primary sources, J. Patrice McSherry provides a hidden history of the Cold War through her analysis of the intelligence networks, security structures, coordinated operations, and international connections of Condor. Revealing new details of Condor operations and fresh evidence of links to the U.S. security establishment, this controversial work offers an original analysis of the use of secret, parallel armies in Western counterinsurgency strategies. It will be a clarion call to all readers to consider the long-term consequences of clandestine operations in the name of "democracy.""--Jacket